Orden y desorden en la Alameda de la ciudad de México durante la segunda mitad del siglo XVIII - López Hernández, Mariana (El Colegio de México, A.C., 2025)
The Mexico City Alameda is a public space that has seen military interventions for policing purposes since the 1760s. Analyzing the Municipality Acts of the capital of the Viceroyalty of New Spain allows us to understand the place as a regulated site for promenades, integrated into recreational, ceremonial and commercial activities. Pictorial sources, manuscripts and the press reveal jurisdictional overlap due to military interventions at this site in order to confront possible disorder, which in turn led to conflict.